Formulation and Antibacterial Activity Test of Salmonella thypimurium and Lactobacillus acidophilus in Microencapsulation of Mangosteen Peel Extract - Andri Kusmayadi; Lovita Adriani; Abun Abun; Muchtaridi Muchtaridi; Ujang Hidayat Tanuwiria (Jurnal Penelitian Pendidikan IPA, 2023)
Xanthone compounds in the ethanol extract of mangosteen peel have antibacterial activity against both pathogenic and beneficial bacteria. The purpose of this study was to examine the effect of various formulations of ethanol extract of mangosteen peel and maltodextrin from palm starch on Salmonella thypimurium and Lactobacillus acidophilus. This research was conducted by culturing the bacterial cultures of S. thypimurium and L. acidophilus on nutrient agar (NA) media in petri dishes according to the Kirby-Bauer method. The NA media that had been made in the petri dish was then made wells to test each treatment as much as 10 ÂµL/disk at various concentrations (100, 75 and 50%). The formulations tested in this study consisted of: T1 (30% ethanol extract of mangosteen peel + 70% maltodextrin), T2 (40% ethanol extract of mangosteen peel + 60% maltodextrin), T3 (50% ethanol extract of mangosteen peel + 50% % maltodextrin), T4 (60% ethanol extract of mangosteen peel + 40% maltodextrin), T5 (70% ethanol extract of mangosteen peel + 30% maltodextrin), T6 (ethanol extract of mangosteen peel only), T7 (maltodextrin only), T8 (positive control containing 100 ppm bacitracin) and T9 (negative control/no treatment). The results of each sample were observed by measuring the sample inhibition zone on the growth medium that had been prepared. Data from the antibacterial activity test results were then analyzed using one-way ANOVA followed by Duncan's test. The results showed that the ethanol extract of mangosteen peel and maltodextrin had a significant effect (P<0.05) on the antibacterial activity of Salmonella thypimurium and Lactobacillus acidophilus. The results of this study indicated that the formulation of ethanol extract of mangosteen peel and maltodextrin had the ability as an antibacterial against Salmonella thypimurium and Lactobacillus acidophilus at a medium level.